The impact of percutaneous endoscopic gastrostomy on nutritional status and survival in cervical esophageal cancer patients undergoing chemoradiotherapy - Wen, Zijun; Liu, Xing; Zhong, Yingqi; Zhou, Haier; Xiao, Guoming; Huang, Zhongying; Chen, Lihui (Frontiers in Nutrition, 2025)
ObjectiveThis retrospective study aimed to study the effects of percutaneous endoscopic gastrostomy (PEG) on nutritional status and overall survival (OS) of cervical esophageal cancer (CEC) patients who received concurrent chemoradiotherapy.MethodsThirty-four CEC patients who underwent concurrent chemoradiotherapy (CCRT) were retrospectively reviewed. A series of nutritional indicators: controlling nutritional status (CONUT) score, weight, body mass index, albumin, lymphocyte counts, hemoglobin (HGB) was introduced to evaluate the nutritional status between patients with or without PEG.ResultsAmong the 34 patients, 18 received PEG placement (PEG group) and 16 did not (Non-PEG group). The median survival for the PEG group was 38.0 months (range, 6.0–60.3), and for the Non-PEG group, it was 43.5 months (range, 21.5–162.8). The 2, 3, and 4 year OS rates for the PEG group were 81.9% (95% confidence interval [CI]: 63.2–100%), 54.3% (95% CI: 25.5–83.1%), and 32.6% (95% CI: 0.0–63.6%), respectively, while the Non-PEG group had 2, 3, and 4 year OS rates of 100% (95% CI: 83.0–100%), 82.1% (95% CI: 59.2–100%), and 49.2% (95% CI: 11.4–87.0%), respectively. There was no significant difference in the OS between the PEG group and the Non-PEG group (p = 0.095, hazard ratio [HR] 0.398, 95% [CI] 0.135–1.173). In the nutritional index, changes in HGB were significantly correlated with PEG (p = 0.016). Multivariate analysis results showed: weight loss ≥5% (p = 0.041, HR = 5.664, 95% CI: 1.075–29.846) and a CONUT score ≥4 (p = 0.01, HR = 15.223, 95% CI: 1.935–119.783) were independent prognostic factors for OS.ConclusionsWeight loss during chemoradiotherapy and higher CONUT scores may decrease the OS rate for CEC patients. However, PEG insertion did not affect the OS rate.